Research on safety in heavy industry / Shahida Abu Hashim, Norlina Mohd Johan and Izdihar Tharazi - Abu Hashim, Shahida; Mohd Johan, Norlina; Tharazi, Izdihar (2003)
Safety can be defined as working without injury and without suffering any illness due to man, material, machine and environment at workplace. Heavy industry is the type of industry that deals with machineries and exposed to more hazards in working. This research on Safety in Heavy Industry explained us on how important safety in our environment of workplaces. As moving to become an industrial country, we should not careless or neglect about the welfares of employees, because they are the main characters to achieve the target. By considering that, our government, nongovernmental bodies, institutional of higher learning and employers and employees themselves are altogether trying to overcome the safety problems while in workplaces. Many activities have been conduct to increase the awareness on safety in one’s life and in working environment. By applying the personal protective equipment and follow the regulations that suggested by Occupational Safety and Health Acts 1994, the safety of the workplaces can be improved. Therefore we have made 2 cases study in heavy industry to know how safety systems are applied. Lastly, the co-operation of all sides is the most important measure should have in solving this problem.